Strengthening of ice with basalt materials - Buznik, Vyacheslav M.; Goncharova, G. Yu; Grinevich, D. V.; Nuzhny, G. A.; Razomasov, N. D.; Turalin, D. O. (Cold regions science and technology)
Practical approaches to controlling the strength and deformation properties of ice reinforced with basalt materials (rovings, fibres and nets) and/or modified by dopants of various groups are discussed in this paper. To carry out the entire research on the strength and deformation properties, approximately a thousand of ICMs samples were produced and tested. The three-point bending tests of ice beams and the compression tests of ice cylinders were carried out by authors. It was shown that the introduction of basalt rovings significantly improves the strength and deformation properties of freshwater ice. Ice reinforcement modifies the mechanism of cracks propagation and the overall nature of the specimens' failure. The major morphological and topological factors involved in the manufacture process of high strength ice composite materials were revealed. A combination of basalt rovings reinforcement and chemical modification of the ice matrix with dopants increases the strength properties of the tested ICM specimens by 4-6 times compared to freshwater ice samples. Based on collected experimental data the corresponding recommendations on the choice of reinforcement parameters are given dependent on the functional purpose of the ice composites being implemented.